Observation of the decay Λ0b → χc1pπ− - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Kopecná, Renata; et al. (Journal of high energy physics, 2021)
The Cabibbo-suppressed decay Λ0b → χc1pπ− is observed for the first time using data from proton-proton collisions corresponding to an integrated luminosity of 6 fb−1, collected with the LHCb detector at a centre-of-mass energy of 13 TeV. Evidence for the Λ0b → χc2pπ− decay is also found. Using the Λ0b → χc1pK− decay as normalisation channel, the ratios of branching fractions are measured to be
Im Titel sind "0" und "-" hochgestellt, „c1“ ist tiefgestellt
The LHCb collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecná, B. Leverington, P. Li, H. Malygina, J. Marks, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, A. Zhelezov [und viele weitere]
Gesehen am 15.02.2022